VARIASI FONOLOGIS DAN LEKSIKAL BAHASA BALI DI DESA LEMBONGAN, NUSA PENIDA - I Nyoman Sutrisna (TELAGA BAHASA, 2016)
Lembongan Village is one of the villages located in the district of NusaPenida. Lembongan Village area includes Ceningan Island and thesouthern part of Lembongan Island. Although they are in one administrative village, the geographical differences cause variations in language use in the village. This study aimed to obtain linguistic conditions contained in Lembongan Village, Nusa Penida District through the description of phonological variation and lexical variations in these areas. In the data collection, it was used field research method by using four informants; two people from Lembongan Island and two people from Ceningan Island, whereas in the data analysis, the method used is frontier method. Discussion of the results shows that there are seven variations of vowel and thirteen variations of consonant sounds. These variations are ə~ ɔ /_k#, ə~aw ̸_#, o~aw/_#, ɛ~ay ̸_#, e~ay /_#, u~u: / _#, a~ə / #k_, n~Ø ̸v_k, m~Ø ̸v_k, ŋ~Ø ̸v_k, n~Ø ̸_#, ?~Ø ̸_#, p~t ̸_#, b~p ̸_#, b~g̸_#, ?~Ø ̸v_k, k~? ̸ v_v, n~ŋ ̸_#, b~Ø ̸ k_v, dan k~t ̸ #_.Lexically, there are also variations in the meaning field of verb, kinship system, adjectives, body parts, and the task word.